KAJIAN LITERATUR: PERAN GURU SEBAGAI TELADAN DALAM PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR DI ERA DIGITAL - Afifah Aulia Fitri; Adi Putra; Petrus Suhendro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the dynamics of the role of teachers as role models in character formation of elementary school students in the digital era through the Systematic Literature Review (SLR) approach. Data were collected from ten national and international scientific articles published in 2019–2025 obtained through systematic searches on Google Scholar and SINTA. The review process followed the PRISMA flow which includes the stages of identification, screening, eligibility, and inclusion of articles. The analysis was carried out thematically by grouping the findings into three main themes, namely: (1) teachers as role models and opinion leaders, (2) contextual and adaptive character learning approaches, and (3) collaboration between teachers, parents, and the school environment. The results of the study show that teachers have a strategic role in shaping students' character through moral role models and the integration of character values ​​in technology-based learning. The challenges of the Society 5.0 era, such as the rapid flow of information and low digital ethics literacy, require teachers to have digital literacy skills and an understanding of cyber ethics. Effective character learning also requires synergy between teachers, parents, and the school community on an ongoing basis. This study provides a conceptual contribution to strengthening the role of teachers in the context of Kurikulum Merdeka, although it is limited to the type of literature analyzed and has not involved quantitative empirical data. Further research with a mixed approach is recommended to test the effectiveness of technology-based character learning models more comprehensively.